PENGARUH KONSEP DIRI DAN KEDISIPLINAN BELAJAR TERHADAP PENGUASAAN KONSEP IPA - DIYAN MARLINA (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2016)
The aim of this research is to determine the influense of self-concept and discipline in learning, either directly or indirectly on mastery of concepts of natural science. The research method used was a survey, with a sample size of 75 students, drawn by simple random sampling technique from primary school in the area of South Jakarta. Data collection used a questionnaires that have been validated and the data values from  the results of the written test students. Data analisys used path analisy, with the first test of normality, linearity test and multikolinearity test. The implications of this study were obtained, namely : that there is a direct influence on the discipline of self-concept study is r12 = 0,617 and P21= 0,617, there is a direct influence on concept mastery learning discipline of natural science is r12 = 0,407 and P21= 0,306, self-concept does not directly influence mastery of concepts of natural science is r13 = 0,352 and P31= 0,163.